The Legal Protection for Consumers in the Digital Economy Era in Facing Challenges and Opportunities - Iskandar, Eka Ardianto; Nugraha, Roby Satya (JURNAL AKTA, 2024)
This research aims to examine the legal aspects of regulating the digital economy in Indonesia, analyze the challenges faced, and identify opportunities that can be utilized to strengthen the existing legal framework. The digital economy in Indonesia is growing rapidly along with advances in information and communication technology. However, this development presents significant legal challenges, ranging from personal data protection, cyber security, to E-commerce and fintech regulations. The research method used is normative juridical analysis with a statutory approach and case studies. The research results and findings show that although there are several regulations governing the digital economy, there are still legal gaps and uncertainties that require further attention from policy makers. This research recommends strengthening regulations and increasing the capacity of law enforcement in dealing with the dynamics of the digital economy.